Sustainable Development, Digital Democracy, and Open Government: Co-Creation Synergy in Ukraine - Khutkyy Dmytro; Matveieva Olga (Comparative Southeast European Studies)
The article examines the interplay between the United Nations Sustainable Development Goals (SDGs), digital democracy, and open government in Ukraine in 2018 and 2020. The authors employ a mixed methods exploratory approach combining desk research with expert interviews. The study finds that during public consultations in Ukraine, the SDGs served as discussion themes, while the Open Government Partnership provided an executable platform. These e-consultations helped collect policy ideas, e-discussions facilitated policy drafting, and non-binding internet voting assisted in prioritising open government draft policies. The Agenda for Sustainable Development framework introduced policies with an education, youth, inclusion, and gender focus to open government. Public consultations increased awareness about the SDGs in Ukrainian civil society and prompted authorities to implement them. The combination of real-life, online, and hybrid consultation formats enabled elements of participatory, direct, and consensus democracy in post-revolutionary and pre-full-scale invasion Ukraine.